Persistence of Fipronil and Bifenthrin Residues in Cabbage - Reddy, C. Narendra; Reddy, D. Jagdishwar; Rahman, S. M. A. S. (International Journal of Bio-resource and Stress Management, 2023)
The experiment was conducted during kharif 2007 with cabbage variety Varun. Three sprays of fipronil @ 100 and bifenthrin @ 50 g a.i. ha-1 respectively were sprayed at head formation stage. The dissipation pattern of fipronil revealed that initial deposit of fipronil (1.69 mg kg-1) was dissipated to below detectable residues at 10 days after third spray. While, in case of bifenthrin, the initial deposit (1.03 mg kg-1) was dissipated below detectable level at 7 days after third spray. The maximum residue limit for fipronil and bifenthrin was found to be 0.2 and 0.1 mg kg-1, respectively. The waiting period for safe harvest of cabbage heads after three sprays of fipronil and bifenthrin @ 100 and 50 g a.i. ha-1 at head formation stage was 5.19 and 5.16 days, respectively. The half life values for fipronil and bifenthrin was 3.13 and 3.38 days, respectively.